2017
DOI: 10.1111/imig.12358
|View full text |Cite
|
Sign up to set email alerts
|

Economic Reintegration of Ethiopian Women Returned from the Middle East

Abstract: Current migration studies and policy reviews neglect the vital link between migration experiences of labour migrants and their return and reintegration process. The objective of this study is to highlight the phenomenon and bring the matter to policy makers’ attention. This study uses in‐depth interviews and a series of focus group discussions to explore the relationship between migration experiences and economic reintegration of unskilled Ethiopian women who are return migrants from Middle Eastern countries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In the current study, however, men reportedly looked for women with economic resources; however, this does not guarantee that the relationship will move on to marriage. Our participants did not display visible economic changes because of their migration experience (see also, Nisrane et al, 2017) and, hence, it was difficult to project what might have happened if they had been able to successfully accumulate economic resources from their migration. This requires further research, but it highlights the possibility that in order to overcome the stigma associated with their migration (such as violation of the chaste rule or passing the accepted marital age), women need to have good economic resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, however, men reportedly looked for women with economic resources; however, this does not guarantee that the relationship will move on to marriage. Our participants did not display visible economic changes because of their migration experience (see also, Nisrane et al, 2017) and, hence, it was difficult to project what might have happened if they had been able to successfully accumulate economic resources from their migration. This requires further research, but it highlights the possibility that in order to overcome the stigma associated with their migration (such as violation of the chaste rule or passing the accepted marital age), women need to have good economic resources.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that some returnees involve in sex work to help their family in the home country or sustain themselves in destination countries. Many of the returnees regret that they spent their young age trying to get money to help their parents and siblings by compromising their own future life in both economic and social terms (see also Grabska et al, 2019aGrabska et al, , 2019bNisrane et al, 2017Nisrane et al, , 2019. To this end, Grabska et al (2019b) stress positive changes that occur through migration are often slow and negative impacts outweigh the positive ones in young girl migrant's life.…”
Section: Discussionmentioning
confidence: 99%
“…In general, research on reintegration in Ethiopia indicates that upon return, Ethiopians mainly strive for economic and social reintegration (Koser & Kuschminder, 2015;Desalegn, 2017;Nisrane et al, 2017), which mirrors the two domains mainly emphasized in the field of reintegration of returnees. For the Ethiopian context, authors raised housing, employment, income and returnee's access to rights and institutions (e.g.…”
Section: Return and Reintegration In Ethiopiamentioning
confidence: 99%
“…For the Ethiopian context, authors raised housing, employment, income and returnee's access to rights and institutions (e.g. land, debt) as indicators of economic reintegration (Michael, 2014; Nisrane et al ., 2017; Kuschminder, 2017). Variables applied to measure social reintegration were related to membership of organizations, friends and family ties, transnational ties, the time duration of stay after return and involvement in the decision‐making process in the household (Adamnesh, 2006; Ketema, 2014; Desalegn, 2017; Bilgili et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in cases of deportation the migrant may be considered a "failed migrant" if they are returned before fulfilling their economic goals. Indeed, the ability to utilize savings from work abroad may be crucial to the returnees' ability to secure a livelihood (Nisrane et al, 2017). We hypothesize that respondents with a good or very good socio-economic position during migration will have a more negative experience of return as their cycle and earning potential was interrupted (H2).…”
Section: The Migration Life Cyclementioning
confidence: 99%